Review: Aktivitas antioksidan dan antibakteri senyawa flavonoid dari ekstrak etanol daun johar (Senna siamea Lamk) - Kinanti, Kinanti (Maliki Interdisciplinary Journal, 2024)
Johar (Senna siamea Lamk) is an annual plant that grows a lot in Southeast Asia. Johar leaves contain many secondary metabolites such as flavonoids. Flavonoid compounds were extracted in 2 different ways, namely by maceration and sonication methods but with the same solvent ethanol. To determine the antioxidant activity of the ethanol extract of johar leaves, it was tested using the DPPH method. The antioxidant activity of the extract was 139.8373 mg/L, which means the activity was moderate. Meanwhile, the antibacterial activity was tested using the diffusion well method. The bacteria used were Staphylococcus aureus, Micrococcus luteus, Escherichia coli and Shigella dysentriane. The results of the antibacterial activity on the four tested bacteria were 14.9 mm (strong), 12 mm (strong), 12.9 mm (strong), and 7.2 mm (moderate). And the antibacterial is a type of bacteriostatic.